Out of context : how to avoid misinterpreting the Bible - Schultz, Richard L. (Grand Rapids, MI : Baker Books, 2012)
Are you guilty of interpretive malpractice? Here's how to prevent it from happening again. Although 92 percent of American households own at least one Bible, only 59 percent read it occasionally, and an even smaller percentage actually study it. It is no wonder that even those of us who value the Scriptures often don't understand them! In "Out of Context," veteran Bible professor Richard L. Schultz uses contemporary examples of "interpretive malpractice" to explain how biblical interpretation can go wrong--and how to get it right. He introduces you to the important concepts of context, word meaning, and genre and the differences between the world of the Bible and our own. With the expert help in interpreting and applying Scripture shared in this book, you'll find your Bible reading more rewarding than ever before.
Includes bibliographical references (p. 143-155).
Keywords: Bible -- Hermeneutics